2016
DOI: 10.1021/acsami.6b04601
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Fabrication of WS2 Nanoplates: Investigation on the Morphology Evolution and Electrochemical Performance

Abstract: Two-dimensional layered chalcogenide WS2, similar to graphene, is considered to be very interesting for materials scientists. However, to make it a useful material platform, it is necessary to develop sophisticated synthesis methods to control its morphology. In this paper, we present a simple approach to prepare various morphologies of WS2 nanostructures by direct thermal evaporation of WO3 and S powders onto Si substrates sputtered with W film without using any nanostructured W-contained precursors and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Their results manifested the electrochemical insertion of Li + into 3R-WS 2 was observed in two different regimes with a transition at about x = 0.2 (Li x WS 2 ), and moreover, they verified the high [146]. Since then, a few attempts were made to investigate the lithium storage activities of WS 2 [24,[147][148][149][150]. A case in point is the use of WS 2 nanotube (synthesized under high-temperature treatment in the presence of H 2 using amorphous WS 3 as raw material) as an anode for LIBs by Wang et al [24] in 2004, and the as-obtained WS 2 nanotube showed a good cycling stability in the wide potential range of 0.…”
Section: Lithium Ion Batteries (Libs)mentioning
confidence: 89%
“…Their results manifested the electrochemical insertion of Li + into 3R-WS 2 was observed in two different regimes with a transition at about x = 0.2 (Li x WS 2 ), and moreover, they verified the high [146]. Since then, a few attempts were made to investigate the lithium storage activities of WS 2 [24,[147][148][149][150]. A case in point is the use of WS 2 nanotube (synthesized under high-temperature treatment in the presence of H 2 using amorphous WS 3 as raw material) as an anode for LIBs by Wang et al [24] in 2004, and the as-obtained WS 2 nanotube showed a good cycling stability in the wide potential range of 0.…”
Section: Lithium Ion Batteries (Libs)mentioning
confidence: 89%
“…The as-proposed vertically grown MoS 2 nanoflowers with ultrathin nanosheets were prepared by CVD in a horizontal quartz tube furnace with two temperature zones working with different heating resistors [30]. By making use of this equipment, we can effectively and accurately control the temperature gradient of the furnace along the quartz tube.…”
Section: Methodsmentioning
confidence: 99%
“…Along with other TMDs, tungsten dichalcogenides have been examined as a potential candidate in lithium‐ion batteries (LIBs) to be used as anode 60–63 . Battery performance would be improved when the electrochemical of the diffusion channels in the 2D layers of TMDs is accessible.…”
Section: Tmds‐ws2 and Mos2mentioning
confidence: 99%
“…Battery performance would be improved when the electrochemical of the diffusion channels in the 2D layers of TMDs is accessible. It has been proved that WS 2 nanosheets exhibit a considerable battery performance when they are deposited vertically on the substrate surface of electrode than horizontally 61 . However, a conductive agent would be required because the electrical conductivity of the particles is not sufficient enough and the cyclability is poor 64,65 .…”
Section: Tmds‐ws2 and Mos2mentioning
confidence: 99%
See 1 more Smart Citation